2015
DOI: 10.4103/0970-9185.155148
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anxiety in patients selecting either general or regional anesthesia for elective cesarean section

Abstract: Background and Aims:We aimed to measure the frequency of preoperative anxiety in patients undergoing elective cesarean section (CS) and its impact on patients decision regarding the choice of anesthesia.Material and Methods:This cross-sectional study included 154 consecutive patients, who were scheduled for elective CS. Visual analog scale (VAS) for anxiety was the study tool, and VAS ≥50 was considered as significant anxiety. Enrolled patients were interviewed by the primary investigator the day before the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 20 publications
(30 reference statements)
5
64
2
6
Order By: Relevance
“…The preoperative anxiety among surgical patients is not routinely performed as part of preoperative patient evaluation and preparation for Anesthesia and surgery (5,(74)(75)(76)(77). However, body of evidences revealed that preoperative anxiety contributed a huge impact on perioperative undesirable outcomes including increased doses of induction agents (11,22,78,79), hemodynamic instability (11,22,27,52,79), cardiac morbidity and mortality in high risk patients (26,51,64,80,81), postoperative pain and increased consumption of analgesics (18,72,74,78,(82)(83)(84)(85)(86), postoperative delirium(87), patient dissatisfaction (88)(89)(90)(91), increased hospital length of stay (29,89,92) and these in turn can incur a signi cant health care cost (1,86,89,92).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preoperative anxiety among surgical patients is not routinely performed as part of preoperative patient evaluation and preparation for Anesthesia and surgery (5,(74)(75)(76)(77). However, body of evidences revealed that preoperative anxiety contributed a huge impact on perioperative undesirable outcomes including increased doses of induction agents (11,22,78,79), hemodynamic instability (11,22,27,52,79), cardiac morbidity and mortality in high risk patients (26,51,64,80,81), postoperative pain and increased consumption of analgesics (18,72,74,78,(82)(83)(84)(85)(86), postoperative delirium(87), patient dissatisfaction (88)(89)(90)(91), increased hospital length of stay (29,89,92) and these in turn can incur a signi cant health care cost (1,86,89,92).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in India revealed that the prevalence of preoperative anxiety was varied from 47-70.3% (27)(28)(29) while the prevalence of preoperative anxiety in Pakistan was ranged from 62-97% (16,22,30).…”
mentioning
confidence: 99%
“…These variables were chosen as they have previously been found to be associated with child preoperative anxiety. 8,26,27 In addition, ANOVA was conducted to examine preliminary differences in mYPAS-SF scores in our 3 ethnic/language groups. Finally, a model of preoperative anxiety was developed that included variables identified in preliminary analyses/extant literature as covariates and ethnicity/language as a predictor.…”
Section: Discussionmentioning
confidence: 99%
“…For categorical demographic and baseline variables, including child's history of previous surgery, parental presence in the operating room and child gender, independent samples t tests were conducted. These variables were chosen as they have previously been found to be associated with child preoperative anxiety . In addition, ANOVA was conducted to examine preliminary differences in mYPAS‐SF scores in our 3 ethnic/language groups.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Bu çalışmada; rejyonal anestezi uygulanan hastalarda, anksiyete skorunun daha düşük çıkmasıyla ve önceden anestezi yönetimi hakkında bilgilendirilen gebelerde, rejyonal anestezi tercih oranları-nın artmasıyla sonuçlanan çalışmalardan yola çıkarak, cerrahi öncesi anestezi yöntemi ile ilgili bilgilendirilen hastalardan, rejyonal anestezi/periferik sinir bloğu yapılacaklarda anksiyete skorları-nın daha düşük olacağı hipotezininin araştırılması, bu hipotezinde STAI ve APAIS testlerini birlikte kullanarak araştırılması ve bu skorlara etki eden faktörlerin değerlendirilmesi amaçlanmıştır. 14,15 …”
unclassified